C-mount packaged laser diode end-pumped passively Q-switched laser with a microlens as pump coupling component. (26th February 2019) - Yang, Houwen; Wang, Bo; Li, Dazhen; Li, Xiaofang; Cheng, Wenyong
Abstract: A microlens has been optimum simulated and designed for an 808 nm laser C-mount packaged semiconductor laser rectangle beam collimation. By designing the suitable focal length, the fast axis light is compressed. After the compression, the fast axis and the slow axis have the same divergence angle, which increases the matching degree between the pump light and the fundamental light. The design for cylinder microlenses collimation system has been discussed in detail. In the laser we designed, the pump source is a C-mount packaged laser diode with controlling the duty cycle of electric pulse. We demonstrate a 63.1 mW, 1 kHz, 779 ps end-pumped Nd:YAG/Cr 4+ :YAG laser at 1064 nm using the above designed microlens capable of compressing fast axis light.